Adult intussusception caused by small bowel lipoma: A case study - Mehanna, Daniel; Mehanna, Patrick (Indian Journal of Case Reports, 2018)
Intussusception in the adult population is an uncommon condition that can present with nonspecific signs and symptoms, both acute and chronic. We present a case of small bowel intussusception due to an underlying submucosal lipoma in an otherwise well 64-year-old lady who presented to the emergency department with a 5-day history of central abdominal pain, nausea, and vomiting with decreasing bowel motions and flatus over the past 2 days. Computed tomography suggested a small bowel obstruction secondary to an intussusception and a small bowel resection was performed. The histopathology revealed a benign submucosal lipoma of the small bowel as a lead point for a small bowel intussusception. Small bowel intussusception is not often considered in the context of a patient presenting with abdominal pain. Its treatment in the adult population, as opposed to the pediatric population, is surgical resection as it is important to exclude an underlying malignancy.